Median ulnar nerve selective blockage versus brachial plexus blockage in carpal tunnel release surgery (Annals of Medical Research, 2021)
Aim: This study aimed to evaluate the feasibility of median ulnar nerve selective blockage vs. brachial plexus blockage in day procedures such as carpal tunnel release surgery. We hypothesized that selective median and ulnar blockage is a feasible classic axillary approach.Material and Methods: This randomized, controlled, double-blind, single-center study included 60 patients. Patients were randomly allocated to two groups; namely, the plexus blockage group (control) and selective group. Patients in the plexus blockage group were administered with 15 ml of local anesthetic for axillary plexus, and in the selective group, 2.5 ml of local anesthetic was applied under USG guidance. We evaluated of full sensory and motor block.Results: The onset of motor block time was observed to be longer and recovery time was shorter in the selective group than in the plexus blockage group (P0.05). Conclusion: Selective nerve block has been shown to be more advantageous than the classic axillary approach of brachial plexus block for day procedures such as carpal tunnel release surgery.Keywords: Carpal tunnel syndrome; brachial plexus blockage; ultrasonography; ulnar nerve block; median nerve block
Keywords: Carpal tunnel syndrome; brachial plexus blockage; ultrasonography; ulnar nerve block; median nerve block